Antiretroviral treatment failure among HIV-positive adults taking first-line therapy and associated risk factors at Adigrat General hospital, Adigart, Ethiopia 2019: A cross sectional study. (2020) - Demsie, Desalegn Getnet; Bantie, Abere Tilahun; Allene, Mengesha Dessie; Alema, Niguse Meles; Gebrie, Desye
Abstract: Background: Human Immunodeficiency Virus (HIV) is a major public health problem globally. Highly active antiretroviral therapy (HAART) has led to profound reduction in the incidence of mortality. However, effective treatment is challenged by the treatment failure. Anti-Retroviral Treatment (ART) Failure may predispose patients to new or recurrent clinical condition. Objective: This study was designed to assess virological and immunological failure of highly active antiretroviral therapy users and associated risk factors at Adigrat General Hospital, Adigrat, Ethiopia. Methods: Institutional based retrospective cross sectional study was conducted. Data were collected by pre-tested structured checklist. The data were entered into Epi-info version 7 and exported into SPSS version 22.0 for analyses. The association between variables was analyzed using multivariate binary logistic regression analysis. The results were presented using text, tables and figure. Result: Seven hundred eighty four patients were included in this study. Of all study participants, 508 (64.8%) were females. More than half participants 376 (47.96%) were in the age range of (31–45) years. The overall prevalence of treatment failure was 27.48%; of this 12.35% of the participants developed immunologic failure and 4.70% of them had both immunologic and virologic failure. Factors that were significantly associated with treatment failure following multivariable analysis were rural resident [AOR = 3.6; 95% CI (1.11–7.36)], WHO stage III/IV [AOR = 2.7; 95% CI (1.21–5.08)], baseline CD4 count (cells/mm 3 ) less than 199 [AOR = 8.11; 95% CI (2.46–19.54)], treatment interruption [AOR = 5.4; 95% CI (2.61–10.45)], poor drug adherence [AOR = 5.9; 95% CI (1.15–12.43)] and TB/HIV co-infection [AOR = 4.6; 95% CI (1.33–12.12). Conclusion: The prevalence of ART failure was higher. Multivariate analysis showed that rural residency, WHO clinical stage III/IV, baseline CD4 count (cells/mm 3 ) less than 200, treatment interruption, poor drug adherence, opportunistic infections and TB/HIV co-infection were significantly associated with treatment failure. Highlights: The overall prevalence of treatment failure was 27.48%. From all participants 12.35% developed immunologic failure. Majority of the patients 433 (55.2%) started second line ART 12 months after stopping first line ART.